2009
DOI: 10.1016/s0022-5347(09)61634-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Sexual Outcomes in Long-Term (5+years) Prostate Cancer Disease Free Survivors After Radical Prostatectomy

Abstract: Background: After long term disease free follow up (FUp) patients reconsider quality of life (QOL) outcomes. Aim of this study is assess QoL in prostate cancer patients who are disease-free at least 5 years after radical prostatectomy (RP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The current study found that SB was associated with age at diagnosis of prostate cancer, marital status and time of assessment since surgery. Other studies have noted similar findings [22,23] and additional associations. Within the CaPSURE database, a study of post prostatectomy men found that those with a high school education or less were more likely to have worse SB then men who were college graduates [10].…”
Section: Discussionsupporting
confidence: 68%
“…The current study found that SB was associated with age at diagnosis of prostate cancer, marital status and time of assessment since surgery. Other studies have noted similar findings [22,23] and additional associations. Within the CaPSURE database, a study of post prostatectomy men found that those with a high school education or less were more likely to have worse SB then men who were college graduates [10].…”
Section: Discussionsupporting
confidence: 68%
“…Because of the smaller sample size of married/partnered participants who completed the DAS measure, the relationship function models only included months of ADT, current sexual function, and sexual bother as independent variables. Those were chosen as the most relevant variables to include based on the literature and conceptual relations among study variables as well as our interest in evaluating the importance of sexual bother in the context of ADT‐related effects on sexual function [21,24,35]. To test whether sexual bother explained a significant amount of unique variance in each outcome, covariates and sexual function were included in step 1 and sexual bother was included in step 2.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these significant physiologic changes, there may be variability in the degree to which men are bothered by ADT sexual side effects [21]. Although most research has been in localized prostate cancer, findings suggest sexual bother may be largely independent of sexual function and uniquely related to QOL outcomes [21–24]. Changes in sexual function occur within the context of other psychosocial and situational factors related to sexuality (e.g., expectations for sexual performance, perceptions of diminished masculinity, having an available partner, and partners' sexual function and interest [18,25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…P rostate cancer (PCa) is the most common non-cutaneous cancer diagnosed in American men [1]. Although 5-year survival rates among men treated for early stage disease approach 100% [1], the adverse impact of treatment on quality of life is a prominent concern and often a basis for treatment selection [2,3]. Men contend with a host of treatment-related complications, including declines in sexual, urinary, and bowel functioning [4].…”
Section: Introductionmentioning
confidence: 99%